Das Nachfeld im Deutschen : Theorie und Empirie - Vinckel, Hélène (Reihe Germanistische Linguistik, 2015)
This is the first study devoted exclusively to the typically overlooked non-sentential usage form of the "postfield" (Nachfeld) in German. The essays present findings from empirical studies and examine theoretical aspects related to syntax, information structure, stylistics/pragmatics, and language acquisition. They address written as well as spoken language from both synchronic and diachronic viewpoints.